Een staker sluit de fabriekspoorten na z'n eisen middels een spandoek kenbaar te hebben gemaakt - Singels, Han, (1982)
Een staker sluit de fabriekspoorten na z'n eisen middels een spandoek kenbaar te hebben gemaakt.